Exploration through teaching reality: encounters with the target motion events - Mamat, Roslina; Mohd Zin, Zaid; Zhaorong, Xu (Universiti Malaysia Pahang Al-Sultan Abdullah, 2024)
All human beings experience motion events (ME) in their daily lives. While understanding and describing ME are universal aspects of human cognition, individuals differ in their capacity to observe, interpret, and convey events (Park, 2022), especially in the foreign language classroom. Since languages have different encoding rules for describing events, teachers need to specify which elements of event representation differ and which are common between typologically different languages such as Japanese and Chinese. There is a body of research that focuses on crosslinguistic differences in the acquisition of ME (Allen et al., 2007; Cadierno, 2008; Laws et al., 2021). However, to facilitate the learning task, it is crucial that learners perceive and utilise cross-linguistic similarities to existing knowledge (Ringbom, 2016).